Impact of primary tumor clinicopathological factors on prognosis after hepatic resection for rectal liver metastases - Tomofumi Uotani; Takeshi Takamoto; Satoshi Nara; Daisuke Ban; Takahiro Mizui; Konosuke Moritani; Shunsuke Tsukamoto; Yukihide Kanemitsu; Tsutomu Fujii; Minoru Esaki (Annals of Gastroenterological Surgery)
Abstract Background Treatment of liver metastases from rectal cancer has been considered based on research data on liver metastases from colorectal cancer. This study aimed to clarify the impact of clinicopathological factors of the primary lesion, including rectal cancer‐specific factors such as lateral lymph node metastasis, on the prognosis after liver resection. Methods This was a single‐center retrospective study of patients undergoing curative surgical treatment for resectable liver metastases from rectal cancer from January 2010 to June 2023. Prognostic factors were investigated using univariable and multivariable analyses. Results The cohort consisted of 113 males and 44 females, with a median age of 60 years. Lateral lymph node dissection was performed in 48 patients, of which 11 had positive nodes. Multivariable analysis revealed lateral lymph node metastasis (HR 5.86; 95% CI 2.40–14.2; p = 0.0001) and perineural invasion (HR 2.83; 95% CI 1.36–5.88; p = 0.005) as independent prognostic factors. After curative hepatectomy, 73.3% of patients with these two factors showed early recurrence within 6 months, requiring nonsurgical treatment. Conclusions Lateral lymph node metastasis and perineural invasion of the primary tumor were prognostic factors after resection of rectal liver metastases. Patients with these factors required nonsurgical treatment in the early postoperative period.